Structural Behavior of Corroded Steel Pipes Subject to Axial Compression and Internal Pressure: Experimental Study - Dewanbabee, Halima; Das, Sreekanta (Journal of structural engineering (New York, N.Y.), 2013)
AbstractExternal corrosion is found in many onshore oil and gas pipelines, and corrosion is a major cause of structural failure of these pipelines. Onshore buried pipelines can be subjected to axial, bending, shear, and other complex loadings as a result of geotechnical movements and temperature variations. In addition, these pipes experience internal pressure from the fluids that they transport. Pipeline industry is concerned about the structural behavior and integrity of corroded pipelines when subjected to various loads and load combinations. Hence, structural behavior and failure conditions of corroded pipelines under various loads and load combinations need to be understood for safe operation of these field pipelines. A literature review did not reveal any studies that determined the structural behavior of corroded steel pipes when subjected to monotonically increasing axial compressive force with constant internal pressure. Therefore, an experimental study was completed to determine the structural behavior of X46 steel line pipe subjected to monotonically increasing axial compression and constant internal pressure as the geometry of corrosion and level of internal pressure change. This study shows that the axial load-carrying capacity reduces as the corrosion depth increases. However, this pipe is highly ductile and does not pose any threat to the structural integrity of the pipe when subjected to monotonically increasing axial deformation and constant internal pressure.